A prototype of a receptive lexical test for a polysynthetic heritage language: The case of Inuttitut in Labrador. (October 2015) - Sherkina-Lieber, Marina; Helms-Park, Rena
This paper describes the process of designing, administering, and assessing a language-sensitive and culture-specific lexical test of Labrador Inuttitut (a dialect of Inuktitut, an Eskimo-Aleut language). This process presented numerous challenges, from choosing citation forms in a polysynthetic language to dealing with a lack of word frequency data. Twenty heritage receptive bilinguals (RBs) with very limited production skills in Inuttitut (their first language) and a comparison group of eight fluent bilinguals (FBs) participated in our study. Since the RBs lacked production skills in Inuttitut, the lexical test required participants to translate a carefully compiled list of Inuttitut nouns and verbs into English. The results revealed that RBs had good comprehension of basic vocabulary (85% accuracy), but differed significantly from FBs, mostly because the RBs had a number of partially accurate translations. The three lowest scoring RBs had the highest number of such translations as well as inaccurate translations based on phonological associations, as is common in emergent lexicons. This lexical test correlates with grammatical proficiency measures, pointing to its potential value as a quick placement and diagnostic test in revitalization programs for Inuttitut as well as other languages in a language loss situation.